2007
DOI: 10.1108/14635770710730955
|View full text |Cite
|
Sign up to set email alerts
|

Simulating less‐than‐truckload terminal operations

Abstract: Purpose -Recent surveys indicate that transportation companies are not utilizing technology in decision making despite growing complexity of transportation systems. This paper aims to present a discrete simulation approach to benchmarking performance measures of terminal operations of less-than-truckload (LTL) freight carriers. Design/methodology/approach -The methodology involves design of heuristics for the dock assignment problem and uses discrete event simulation to evaluate performance of the various heur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…For example, DES has been used to evaluate the performance of a supply chain for chilled food products (Van der Vorst et al 2000), as well as comparing different transport modes in terms of logistics cost, energy use, CO2 emissions, and product quality decay (Van der Vorst et al 2009). DES has also been used to study the terminal operations of a warehouse, which involves loading, unloading, and other warehouse-specific activities (Liong and Loo 2009;Deshpande et al 2007). Liong and Loo (2009) used DES to develop a strategy to optimize the residence time of delivery trucks and found that the truck drivers have to wait in long queues when there is no scheduling of arrivals.…”
Section: Methodsmentioning
confidence: 99%
“…For example, DES has been used to evaluate the performance of a supply chain for chilled food products (Van der Vorst et al 2000), as well as comparing different transport modes in terms of logistics cost, energy use, CO2 emissions, and product quality decay (Van der Vorst et al 2009). DES has also been used to study the terminal operations of a warehouse, which involves loading, unloading, and other warehouse-specific activities (Liong and Loo 2009;Deshpande et al 2007). Liong and Loo (2009) used DES to develop a strategy to optimize the residence time of delivery trucks and found that the truck drivers have to wait in long queues when there is no scheduling of arrivals.…”
Section: Methodsmentioning
confidence: 99%
“…Truck scheduling in this setting reduces to assigning outbound destinations to outbound doors over a predefined planning horizon and nightly scheduling inbound trucks based on a given outbound door assignment. Static door assignments are employed by the majority of papers addressing truck scheduling in less than truckload (LTL) terminals in which the operations are typical crossdocking operations [16]. There is also one variation of static door assignments practiced in "production crossdocks"…”
Section: Operational Strategiesmentioning
confidence: 99%
“…Resource unavailability is generally represented as delays in the scheduling length. Addressing a scheduling problem in a resource-constrained environment is much more complicated [8,9,[21][22][23][36][37][38][39][40][41][42][43][44][45][46][47] crossdocking exclusive [6,8,9,[16][17][18][21][22][23] [ 25-35, 38-41, 43, 47] mixed [36,37,[44][45][46] scheduling synchronous [6,8,9,17,18,[25][26][27][28][29] [ [31][32][33][34][35][36][37][38]…”
Section: Operational Strategiesmentioning
confidence: 99%
See 2 more Smart Citations